Fast and blister-free irradiation conditions for cross-linking of PMMA induced by 2 MeV protons - Somrit Unai (2018)
For soft lithography, the conventional negative tone resists, such as SU-8, that are used to create the mold have a number of drawbacks. PMMA, which is normally used as a positive tone resist, can be used as a negative resist by using high-fluence irradiation conditions. In this report, we outline optimization of the irradiation conditions for PMMA thin films using 2 MeV H + ions to exploit their ability to work as a negative tone resist at ion fluences above 1.0 × 10 15 ions cm -2 . The main aim was to induce cross-linking while maintaining the exposed regions free of blisters and maintaining short irradiation times. We found that by using a two-step process with a low-flux irradiation, followed by a high-flux irradiation, the exposure time could be shortened by ∼50%. We also found that ion fluences greater than 5.0 × 10 15 ions cm -2 minimized the distortion in stitched regions. © 2011 Elsevier B.V. All rights reserved.